The Influence of Store Atmosphere, Customer Delight and Product Completeness on Consumer Loyalty in Groceries Retail MSMES Suko Asri Market Kab. Sidoarjo - Annisa Kaffi; Siti Mujanah (Journal of Applied Management and Business, 2023)
This study aims to determine the effect of Store Atmosphere, Customer Delight and Product Completeness on Consumer Loyalty in MSME Retail Groceries Suko Asri Market, Sidoarjo. This type of research is quantitative research. The population is all MSME Retail Groceries customers at Suko Asri Market, Sidoarjo. The number of samples is 75 people with purposive sampling process. Target customers who have shopped more than 1 time at MSME Retail Groceries Pasar Suko Asri Sidoarjo. The data collection method uses a survey method with a questionnaire as an instrument. Test the instrument using the Validity and Reliability Test, Multiple linear regression, Classical Assumption Test, t test and E2 test. From the results of the F test value, it shows that Store Atmosphere, Customer Delight and Product Completeness both have a significant effect on consumer loyalty, MSME Retail Grocery Market, Suko Asri Sidoarjo Market. Meanwhile, the results of the t test show that (1) Store atmosphere has an effect on consumer loyalty, (2) Customer delight has an effect on consumer loyalty, (3) Product completeness has an effect on consumer loyalty in MSMEs Retail Groceries Suko Asri Market, Sidoarjo.